(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2024)
The article analyzes the impact of income inequality on food security using examples from developing countries. This analysis demonstrates that as the level of income inequality increases, access to food for the lower strata of the population becomes limited, which in turn negatively affects their health and overall well-being. In developing countries, significant income disparities pose serious risks to food security, especially in impoverished regions. The relationship between income inequality and food security is also linked to factors such as social and economic policies, agricultural reforms, and global trade policies. The article includes recommendations on ways to reduce income inequality and ensure food security, while summarizing existing research and practices related to this topic.